Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1140/epja/i2018-12498-1
|View full text |Cite
|
Sign up to set email alerts
|

A meson-baryon molecular interpretation for some $\Omega_{c}$ Ω c excited states

Abstract: We explore the possibility that some of the five narrow Ωc resonances recently observed at LHCb could correspond to pentaquark states, structured as meson-baryon bound states or molecules. The interaction of the low-lying pseudoscalar mesons with the ground-state baryons in the charm +1, strangeness −2 and isospin 0 sector is built from t-channel vector meson exchange, using effective Lagrangians. The resulting s-wave coupled-channel unitarized amplitudes show the presence of two structures with similar masses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 82 publications
6
49
0
Order By: Relevance
“…Several other works [17,18,19,20] have also addressed the possibility of interpreting of some of the Ω c states seen at CERN as quasi-bound meson-baryon systems, as well as the prediction of analogous states in the bottom sector [21], finding results which are similar to those of our work [16] and hinting that the meson-baryon description cannot be ignored when trying to understand the nature of these excited heavy baryons.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Several other works [17,18,19,20] have also addressed the possibility of interpreting of some of the Ω c states seen at CERN as quasi-bound meson-baryon systems, as well as the prediction of analogous states in the bottom sector [21], finding results which are similar to those of our work [16] and hinting that the meson-baryon description cannot be ignored when trying to understand the nature of these excited heavy baryons.…”
Section: Discussionsupporting
confidence: 80%
“…The G l function for the meson-baryon loop is regularized using the dimensional regularization approach, which introduces the dependence on a subtraction constant a l (µ) for each intermediate channel l at a given regularization scale µ (see Eq. (18) in [16]).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[7] two Ω c resonant states at 3050 MeV and 3090 MeV were generated with spin-parity J P = 1/2 − , reproducing two of the experimental states. Also, within an extended local hidden gauge approach that incorporates low-lying 1/2 + and 3/2 + baryons together with pseudoscalar and vector mesons [8], two J P = 1/2 − Ω c states and one J P = 3/2 − Ω * c were observed, the first two in good agreement with the outcome of [7].…”
Section: Introductionmentioning
confidence: 93%
“…Besides, both Refs. [21,22] interpreted some Ω 0 c excited baryons as meson-baryon molecular states. To study the structure of the observed Ω [23].…”
mentioning
confidence: 99%